HUBUNGAN KEPUASAN MAHASISWA FE TERHADAP FASILITAS: DAN KINERJA DOSEN FE DI UNIVERSITAS KRISTEN INDONESIA - R, Randita; Tobing, Fenny BNL (Universitas Kristen Indonesia, 2016)
University is a business engaged in services. Factors that may affect student satisfaction in using the services of a university is the facility. Facilites are physical resources that must exist before a service can be offered to consumers. The next factor affecting student satisfaction is a lecture performance, can not be denied if the student is satisfied with the academic services provided by a lecturer then this can be viewed as a competitive advantage. Lecturer is an important component in service to the students because the university lecturers who provide direct services to students. This study aims to determine the extent to which the level of student satisfaction and performance of the facility Faculty of Economy & Faculty of Economy lecturer at the Indonesian Christian University and what attributes the cause of student satisfaction and performance facility Faculty of Economy lecturer at the Indonesian Christian University. Source data used are primary data obtained through questionnaires to 82 respondents, namely the Indonesian Christian University students, while secondary data obtained through library research by reading books marketing concepts and other data sources that are still associated with this research.Keywords: satisfaction, importance and performance